How mindfulness training may mediate stress, performance and burnout - Furrer, P.; Moen, F.; Firing, K. (The Sport Journal, 2015)
The aim of this article was to explore the influence of mindfulness training on stress, perceived performance in school and sports, and athlete burnout among junior elite athletes. One goal was to determine the usefulness of mindfulness training in performance enhancement and burnout prevention in junior elite sports. A mindfulness-training program (MTP) was conducted with 29 junior elite athletes over a period of 12-weeks. Six of the athletes who were participating in the MTP were randomly chosen to voluntarily participate in a semi structural interview that explored possible effects from the MTP. Our qualitative analyses showed that the mindfulness intervention had a positive impact on the athletes` awareness and recovery. The authors also discuss positive effects on the athletes` focus and performances. The findings are discussed against the usefulness of mindfulness training in athlete burnout prevention.